2017
DOI: 10.1038/ncb3529
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial respiratory chain is essential for haematopoietic stem cell function

Abstract: Adult and fetal hematopoietic stem cells (HSCs) display a glycolytic phenotype, which is required for maintenance of stemness; however, whether mitochondrial respiration is required to maintain HSC function is not known. Here we report that loss of the mitochondrial complex III subunit Rieske iron sulfur protein (RISP) in fetal mouse HSCs allows them to proliferate but impairs their differentiation, resulting in anemia and prenatal death. RISP null fetal HSCs displayed impaired respiration resulting in a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
217
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(227 citation statements)
references
References 59 publications
(60 reference statements)
9
217
1
Order By: Relevance
“…Therefore, 2HG may provide cells with a reservoir of reducing equivalents, and the ␣KG-2HG exchange maintains cellular redox balance. Consistent with this idea, a recent study in hematopoietic stem cells reported that loss of the mitochondrial complex III subunit Rieske ironsulfur protein results in impaired mitochondrial respiration, increased NADH/NAD ϩ ratio, and increased 2HG levels, accompanied with DNA and histone hypermethylation (62). Because L2HGDH activity is dependent on active complex III (63), loss of complex III activity both increases NADH/NAD ϩ and impairs L2HGDH activity to favor 2HG production.…”
Section: Minireview: O 2 Availability and Metabolism In Cancersupporting
confidence: 58%
“…Therefore, 2HG may provide cells with a reservoir of reducing equivalents, and the ␣KG-2HG exchange maintains cellular redox balance. Consistent with this idea, a recent study in hematopoietic stem cells reported that loss of the mitochondrial complex III subunit Rieske ironsulfur protein results in impaired mitochondrial respiration, increased NADH/NAD ϩ ratio, and increased 2HG levels, accompanied with DNA and histone hypermethylation (62). Because L2HGDH activity is dependent on active complex III (63), loss of complex III activity both increases NADH/NAD ϩ and impairs L2HGDH activity to favor 2HG production.…”
Section: Minireview: O 2 Availability and Metabolism In Cancersupporting
confidence: 58%
“…We showed previously that the mitochondrial fusion protein, Mitofusin 2 (Mfn2), is required for the maintenance of HSCs with extensive lymphoid potential, and that this effect was mediated through enhanced buffering of intracellular calcium by mitochondria (Luchsinger et al, 2016). Though recent publications do indicate an important role for respiration in HSC maintenance as well (Anso et al, 2017; Bejarano-Garcia et al, 2016; Guitart et al, 2017), these findings suggest that mitochondria perform specific and essential roles in HSCs, including but likely not limited to calcium buffering, that may not be directly dependent on ATP production. We therefore suggest that the role of mitochondria in the biology of HSCs may need to be revisited.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast to most mature cells, HSCs rely predominantly on glycolytic ATP production (Ito and Suda, 2014; Shyh-Chang et al, 2013; Simsek et al, 2010; Takubo et al, 2013). While shown to be important for HSC maintenance (Anso et al, 2017; Bejarano-Garcia et al, 2016; Guitart et al, 2017), some experimental data suggest that mitochondrial respiration may indeed be more dispensable for HSCs than for progenitors (Norddahl et al, 2011; Yu et al, 2013). Consistent with their reduced mitochondrial respiration, HSCs have been reported to be endowed with low mitochondrial mass based on staining with mitochondrial dyes (Mantel et al, 2012; Mohrin et al, 2015; Romero-Moya et al, 2013; Simsek et al, 2010; Takubo et al, 2013; Vannini et al, 2016; Xiao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that loss of HSCs occurred during ontogeny, and independent of tissue context (both in the prenatal liver and in postnatal bone), further confirms that these phenotypes are cell autonomous. Mitochondrial dysfunction causes attrition of the hematopoietic system, 49,50 and a genomic DNA damage-dependent communication between the nucleus and mitochondria, leading to mitochondrial attrition, has been associated with aging-related pathologies. 38,51,52 Although Rev1 is not found in mitochondria, 53 viable Rev1Xpc and, to some extent, also Rev1 bone marrow cells develop mitochondrial dysfunction suggesting that nuclear replication stress affects mitochondrial activity.…”
Section: Discussionmentioning
confidence: 99%